PENGARUH DIGITALISASI ARSIP TERHADAP KECEPATAN PELAYANAN ADMINISTRASI DI PUSKESMAS MATARAM - Nurul Kamilah; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2026)
Healthcare administration is a crucial element in supporting smooth operations and accurate patient information in primary healthcare facilities. This study aims to analyze the impact of archive digitization on the speed of administrative services at the Mataram Community Health Center (Puskesmas), West Nusa Tenggara. The method used is a literature study (library research) by collecting and analyzing data from various relevant scientific sources such as Google Scholar and government journal portals. The results of the discussion indicate that the transition from conventional archiving to digital systems, such as Electronic Medical Records (RME) and SIMPUS, can significantly reduce patient waiting times through instant data access using NIK or medical record numbers. Digitalization acts as an accelerator that eliminates physical bureaucratic barriers and minimizes the risk of document loss. However, the main challenge faced is the readiness of human resources who still experience technological stuttering. Therefore, a structured staff training and development program is needed, including technical workshops and a peer-to-peer mentoring system to ensure the system's suitability and service efficiency.